Contested energy transition? Europeanization and authority turns in EU renewable energy policy - Solorio, I.; Jörgens, H. (Journal of European Integration, 2020)
In a context of multiple crises, the European Union’s climate and energy policies have become highly politicized and contested. Based on a comparative study of renewable energy policies in ten EU member states, and adopting a circular view of policy change and Europeanization to account for overlapping sovereignty claims between the national and the European level, this article unravels the authority debates over successive rounds of negotiation, adoption, and implementation along three EU directives. Following an exploratory process-tracing method, we investigate how policymaking authority originally delegated to the EU becomes contested by the member states and how these authority conflicts are managed. We find that the Europeanization of renewable energy policy is accompanied by an issue-specific renegotiation of authority between the EU and its member states which, in times of crises, can trigger instances of de-Europeanization and even a partial weakening of European integration in this policy domain.